Effect of harvesting time on seed quality of two bell pepper cultivars (Capsicum annuum) - Mónica B. Ruiz; Carlos A Parera (Revista de la Facultad de Ciencias Agrarias, 2017)
The maturation status of seeds is fundamental at the harvest time to get high rates of germination and vigor. The aim of this study was to determine the effect of harvest time on the quality of pepper seeds. The trial was conducted in two bell type cultivars: Fyuco INTA and Lungo INTA. Fruits were harvested at 4, 5, 6, 7, 8 and 9 weeks after anthesis. Starting from the eighth week the average seed weight stabilized, coincidently with the change in the fruit colour to red. Germination percentage increased linearly as it increased the age of the seed. The electrical conductivity of the leachate was also stabilized in seeds got from fruit harvested from 8 weeks after anthesis, showing that they had reached physiological maturity. The results demonstrate to harvest the fruits of pepper cv Fyuco INTA and Lungo INTA with over 8 weeks of age after anthesis to reach high quality seeds.